(Un-)Writing masculinity : narrative, representations of masculinity, and (un-)writing the Aristotelian dramatic form - Lotter, Matthew (My University, 2018)
Dominant theatre narrative structures are inherently gendered. Feminist theatre theory maintains that the traditional ‘three-act’ structure centralises masculine subject arcs and marginalises the feminine. This single climax structure progresses the plot in a manner which validates masculine qualities, and concludes in a resolution which reifies masculine hegemony, and validates patriarchal gender division of labour, and structural misogyny. Feminist theatrical studies have examined the extent to which the female character is ‘objectified’ through this ‘three-act’ structure to conclude in the image of the patriarchal feminine ideal. Feminist theatre has evolved to counter the patriarchal gender ideology of dominant theatrical practice, the ‘male dramatic form,’ by ‘moving toward’ a feminist poetics which explores the female subject and femininity outside patriarchal binary gender stereotyping. This research aims then to rethink the representation of masculinities and its impact on and through dominant ‘three-act’ structure poetics. Using Athol Fugard’s Sorrows and Rejoicings (2002) as case study, this research seeks to utilise men’s studies and theories of masculinity to interrogate the structural influence of patriarchal ‘masculine’ gender ideology on the ‘male dramatic form’ and its ‘male’ subject. Specifically this research aims to interrogate the extent to which the ‘male’ subject is characterised as an exemplar of hegemonic masculinity: an agent of force and conflict; and its impact on and through the progression of a ‘three-act’ structure. This research will then induce a practical deconstruction of these theoretical interrogations, through a scripted reinterpretation of Sorrows and Rejoicings, to reshape thinkings on theatrical writings of masculinities in ways which don’t reinsert patriarchal gender binaries. By deploying a nuanced reading of the relation between narrative-structure and masculinities, this research will attempt to reinterpret theatrical staging and narrative interventions interceded on behalf of gender by feminist theatre to gauge the extent to which narrative can be manipulated to render the male subject and masculinities outside patriarchal binary gender stereotyping. I hope to question how dominant theatrical narratives ‘write’ masculinity, to incite tractable narrative explorations of the complexities of masculine gender performance. I hope to contribute to an understanding of critical and subversive interventions in existing studies, seeking to (un-)write and re-stage masculinities, and make inroads towards a gendered ‘poetics’ inclusive of non-patriarchal defined masculine characters.
A research report submitted for the degree of Master of Arts in Dramatic Art by Research and Creative Project, University of the Witwatersrand, Johannesburg, 2018
Keywords: Feminist theater; Women in the theater; English drama--Women authors